Analyse généalogique et structure de la population. L’ascendance des natifs de la vallée de la Valserine (Jura français), XVIIe-XXesiècles - Guy Brunet; Stéphane Lallich; Alain Bideau (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Using the parish and civil records of five townships of the Valserine Valley, we have reconstructed the genealogical networks of all the individuals born in this valley from the end of the 17th century to the present day. Our goal is to make a quantitative analysis of these genealogical networks to characterise this population. Is this population homogeneous or can we find several groups with contrasting genealogical histories? Our analysis shows the existence of two groups of natives: the individuals with at least one ancestor present in the valley, in each generation, from the end of the 17th century, and those whose local ancestry is not continuous. This observation can be made whatever the period of birth studied and it reveals the existence of a genealogical structure in the population. We also propose an original method to calculate a coefficient of loss (absolute and relative) of the genealogical information between the second and the fourth ascending generation. Finally, we take up the conclusion of a previous study (Heyer 1993) but by showing that this population structure (a permanent stable nucleus with constant flows of immigrants and emigrants) is not a construction observed only during the 20th century due to recent migrations. In fact, the same observation can be made for the individuals born at the beginning of the 18th century. The SOSA rankings of the ancestors show a relation between the probability for a genealogical line to stay in the valley and the sex of the ancestors born in the valley.